Pembelajaran Daring Dengan Metode Resitasi Dan Pemanfaatan Google Classroom Pada Pembelajaran IPS - Muhammad Denny Wicaksono; Nanis Hairunisya; Nafik Umurul Hadi (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2021)
The covid-19 pandemic, which has infected some Indonesians, led to learning done by learning from home (BDR) method. This study aims to describe online learning by recital method and make use of google classroom in grade IX IPS learning at SMP negeri 2 Sendang. This study uses descriptive qualitative research methods. In this design, the researchers described the phenomenon of the research object, gathered and informed information about the phenomenon of the research object, and reported it narratively about the information that had been found. The location of this research is SMP Negeri 2 Sendang located in Kedoyo Village, Sendang District, Tulungagung Regency. The data collection used in this study is a method of observation, interview, and documentation. The result of this study is that teachers are very capable of managing online classes, students respond positively to online learning, learning consists of five steps. Obstacles in learning are the limitations of student internet quota, stable student internet, and sudden power outages, the solutions include using wifi, waiting for PLN electricity to turn on. Granting internet quota kemendikbud, prioritize 3G network